1997
DOI: 10.1016/s0025-6196(11)63597-0
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer in a Man With Human Immunodeficiency Virus Infection

Abstract: Non-acquired immunodeficiency syndrome (AIDS)-defining neoplasms are being increasingly recognized in patients infected with the human immunodeficiency virus (HIV). The incidence of Hodgkin's disease and seminoma has recently been reported to be increasing in these patients. This article describes the second case of breast cancer in an HIV-infected male patient. A total of 11 cases of coincident breast cancer and HIV infection have previously been reported. It may be prudent to consider breast cancer in the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Early in the HIV epidemic many authors perceived that BC, in the setting of HIV infection, tends to occur at a relatively early age, usually with increased bilateral disease, unusual histology and early metastatic spread, resulting in a poor outcome and early relapse . 10,19,36,41,83,84 Over time, as more data appeared in the literature, this statement has been refuted. 85,73 In their updated case series from Harlem, New York, Sarhan and Oluwole demonstrated that the cancer stage, pathological cancer characteristics and survival outcome was similar in HIV-positive and HIV-negative patients.…”
Section: Clinical and Pathological Characteristics Of Bc In Plwhamentioning
confidence: 99%
See 1 more Smart Citation
“…Early in the HIV epidemic many authors perceived that BC, in the setting of HIV infection, tends to occur at a relatively early age, usually with increased bilateral disease, unusual histology and early metastatic spread, resulting in a poor outcome and early relapse . 10,19,36,41,83,84 Over time, as more data appeared in the literature, this statement has been refuted. 85,73 In their updated case series from Harlem, New York, Sarhan and Oluwole demonstrated that the cancer stage, pathological cancer characteristics and survival outcome was similar in HIV-positive and HIV-negative patients.…”
Section: Clinical and Pathological Characteristics Of Bc In Plwhamentioning
confidence: 99%
“…The evidence presented will be interpreted in the context of three historical time frames: pre-HAART, early HAART and HAART. While BC does occur in men living with HIV/AIDS (MLWHA), 10 this review will mainly focus on BC in women living with HIV/AIDS (WLWHA). Kaposi’s sarcoma (KS) and non-Hodgkin’s lymphoma (NHL) that may also have localized to the breast in PLWHA, 11-13 falls outside the scope of this review.…”
Section: Introductionmentioning
confidence: 99%
“…While there are various reports on the poor response of HIV-positive women to chemotherapy, reports of radiation toxicity could not be identified 82-84 . Radiation has been reported to be well tolerated in patients treated to 64.8 and 65Gy 85,86 . There is insufficient evidence to recommend any treatment modifications of HIV-positive women with breast cancer.…”
Section: Radiosensitivity In Tumors Common To the General Populationmentioning
confidence: 99%
“…Plasmacytoma and Kaposi sarcoma have recently been reported to present as breast masses or breast enlargement in HIV-infected individuals [16,17]. Multiple cases of breast carcinoma in HIV-infected patients (most of whom were women [18][19][20]; less often, they were men [21,22]) have also been described. These cases have spurred some debate about whether a relationship exists between breast cancer and HIV infection, although no definite link has ever been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Because breast carcinoma is rare in male patients [15], most cases of breast enlargement in HIV-infected patients have been presumed to be benign. However, there have been recent reports of various malignancies presenting in the breasts of HIV-infected men, including Kaposi sarcoma [16], plasmacytoma [17], and carcinoma [18][19][20][21][22]. In addition, non-Hodgkin lymphoma (NHL) may rarely present as a breast mass [23], although this has not been reported specifically in an HIV-infected individual.…”
mentioning
confidence: 99%